Insiders and incomers: how lay public health workers' knowledge might improve public health practice. (28th March 2017) - Yoeli, Heather; Cattan, Mima
Abstract: Since 2005, health trainers and other lay public health workers (LPHWs) have been increasingly active in the UK. Although elsewhere in the world LPHWs are expected to come from the communities within which they work and know that their knowledge is valued, neither is the case for LPHWs in the UK. This study sought to discover the lay knowledge of health trainers and other LPHWs, aiming to ascertain how this knowledge might more effectively be utilised within UK public health services. This paper describes a participatory and ethnographic case study research project undertaken on an anonymised urban estate in North East England. Findings were generated by a range of means including by participant observation and semi‐structured interviews. Seven LPHWs took part, as did 32 other community members. This study found that the lay health knowledge of an individual UK LPHW is determined primarily by his or her position within, or in relation to, the community within which he or she works. Insider LPHWs possess an embodied knowledge and incomer LPHWs possess an experiential knowledge which, although different from one another, are essentially interpersonal in nature. Lay health knowledge can take different forms, and different LPHWs can provide different forms of lay health knowledge. Public health structures and services in the UK should make better use of all forms of LPHW knowledge, and should seek from LPHWs training on how to engage the most 'hard‐to‐reach' or 'difficult‐to‐engage' groups. Services recruiting LPHWs should decide whether they are seeking embodied insider LPHW knowledge, experiential incomer LPHW knowledge or a mixture of both.